الآثار النفسية المرتبطة بتعرض العمال للمواد الكيميائية - إسعادي, فارس; سعداني, عبدالرزاق (جامعة الوادي - University of Eloued, 2022)
ملخص: أصبح التعرض للمواد الكيميائية مرافقا لكل نشاطات حياتنا، وبهذا يعتبر من العوامل المؤثرة في تغيرات كثيرة للسلوكيات، كما لها تأثيرات نفسية مختلفة على جميع الأفراد وبدرجات متفاوتة، ما يجعل البعض يشعر بالضغط وسيطرة المشاعر السلبية مثل : الحزن، القلق، والإحباط، والاكتئاب، قد تؤثر في نهاية المطاف بشكل سلبي على المناعة الصحية والنفسية وعلى الصحة العقلية ولقد هدفت هذه الدراسة إلى تسليط الضوء على أثرهـا وطرق الوقاية منها في أماكن العمل. Abstract: Exposure to chemicals has become associated with all our life activities, and therefore it is considered as one of the factors influencing many changes in behavior,It has different psychological effects on all individuals to varying degrees, causing some to feel stress and causing negative emotions. Such as: sadness, anxiety, frustration and depression, it may eventually negatively affect health, psychological immunity and mental health. This study aimed to shed light on its impact and ways to prevent it in the workplace, by reviewing the literary heritage that dealt with this topic.
مقال
Keywords: الاثار النفسية ; العمال,صحة العاملين,مواد كيمياوية; Chemicals ; Psychological effects; Workers health